Calmodulinopathy: Functional Effects of CALM Mutations and Their Relationship With Clinical Phenotypes - Badone, Beatrice; Ronchi, Carlotta; Kotta, Maria-Christina; Sala, Luca; Ghidoni, Alice; Crotti, Lia; Zaza, Antonio (Frontiers in Cardiovascular Medicine, 2018)
In spite of the widespread role of calmodulin (CaM) in cellular signaling, CaM mutations lead specifically to cardiac manifestations, characterized by remarkable electrical instability and a high incidence of sudden death at young age. Penetrance of the mutations is surprisingly high, thus postulating a high degree of functional dominance. According to the clinical patterns, arrhythmogenesis in CaM mutations can be attributed, in the majority of cases, to either prolonged repolarization (as in long-QT syndrome, LQTS phenotype), or to instability of the intracellular Ca2+ store (as in catecholamine-induced tachycardias, CPVT phenotype). This review discusses how mutations affect CaM signaling function and how this may relate to the distinct arrhythmia phenotypes/mechanisms observed in patients; this involves mechanistic interpretation of negative dominance and mutation-specific CaM-target interactions. Knowledge of the mechanisms involved may allow critical approach to clinical manifestations and aid in the development of therapeutic strategies for “calmodulinopathies”, a recently identified nosological entity.